2008
DOI: 10.1111/j.1365-2141.2008.07262.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate tumour suppressor gene loci for Hodgkin and Reed‐Sternberg cells by characterisation of homozygous deletions in classical Hodgkin lymphoma cell lines

Abstract: SummarySeveral tumour suppressor genes (TSG) have been identified as a result of mapping homozygous deletions in cancer cells. To identify putative TSG involved in the pathogenesis of classical Hodgkin lymphoma (cHL), we investigated four cHL cell lines (L428, HDLM2, KMH2, L1236) using four different array-Comparative Genomic Hybridisation (array-CGH) platforms and focused on high resolution identification of homozygous deletions. Out of 79 candidate regions of bi-allelic loss identified by array-CGH, besides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…[7] In another array CGH study of 4 HL cell lines, 47 potential tumor suppressor genes were identified. [8] More recently, a whole-exome DNA sequencing study of 7 HL cell lines identified 463 mutated genes. [9] In a recent study of primary flow-sorted HRS cells, [10] a large number of genomic gains and losses were identified, with a median of 75 genomic segments lost and gained per case.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In another array CGH study of 4 HL cell lines, 47 potential tumor suppressor genes were identified. [8] More recently, a whole-exome DNA sequencing study of 7 HL cell lines identified 463 mutated genes. [9] In a recent study of primary flow-sorted HRS cells, [10] a large number of genomic gains and losses were identified, with a median of 75 genomic segments lost and gained per case.…”
Section: Introductionmentioning
confidence: 99%
“…Gene fusion AML (Ono et al, 2002;Kadkol et al, 2006;Cerveira et al, 2008) Melanoma (Jaeger et al, 2007) SEPT7 Downregulation Glioma (Nagata et al, 2000;Jiang, 2002;Jiang, 2004;Jia et al, 2010;Tanaka et al, 2010) SEPT8 None None None SEPT9 Amplification/ Breast (Montagna et al, 2003;Scott et al, 2005;overexpression Gonzalez et al, 2007overexpression Gonzalez et al, , 2009) Upregulation Ovary Gene fusion AML, ALL (Strehl et al, 2006;Gulten et al, 2009;Saito et al, 2010) (Santos et al, 2010a,b) (Osaka et al, 1999;Yamamoto et al, 2002;Strehl et al, 2006;Kreuziger et al, 2007) Hypermethylation Colon and head and neck (He et al, 2010;Tierling et al, 2010;Quyun et al, 2010) (Grutzmann et al, 2008;deVos et al, 2009) (Bennett et al, 2008;Lofton-Day et al, 2008;Stanbery et al, 2010) Deletion Ovary, breast Russell et al, 2000) Hodgkin lymphoma (Giefing et al, 2008) SEPT10 None None SEPT11 Gene fusion Deletion AML (Santos et al, 2010b;Stevens et al, 2010) Deletion Liver SEPT12 None None SEPT13 None None SEPT14 None None (Montagna et al, 2003) and the Russell group established that SEPT9 overexpression occurs in various human tumors (Scott et al, 2005). The discovery of DNA hypermethylation at the promoter region of SEPT9 in colorectal (deVos et al, 2009) and head and neck cancer patients (Bennett et al, 2008) complicated the conflicti...…”
Section: Sept6mentioning
confidence: 99%
“…located at translocation/insertion breakpoints, identified by copy number analysis, have been frequently associated with cancer (43)(44)(45)(46)(47)(48)(49). No chimeric genes could be cloned in other samples.…”
Section: Discussionmentioning
confidence: 99%